The construction of national identity in Taiwan's media, 1896-2012 - Hsu, Chien-Jung (Brill, 2014)
The Construction of National Identity in Taiwan's Media, 1896-2012 provides the most comprehensive analysis of the development of Taiwan's media and the formation of national identity in Taiwan's media from 1896 to 2012.